Astrocytic Ca2+ Signaling in Epilepsy - Heuser, Kjell; Enger, Rune (Frontiers in Cellular Neuroscience, 2021)
Epilepsy is one of the most common neurological disorders – estimated to affect at least 65 million worldwide. The majority of epilepsy research has so far focused on how to dampen neuronal discharges and to explain how changes in intrinsic neuronal activity or network function cause seizures. As a result, pharmacological therapy has largely been limited to symptomatic treatment targeted at neurons. Given the expanding spectrum of functions ascribed to the non-neuronal constituents of the brain, and in particular astrocytes, in both physiological brain function and in brain disorders, it is natural to look for roles of astrocytes in epilepsy. It is now widely accepted that astrocytes are key controllers of the composition of the extracellular fluids, and may directly interact with neurons by releasing gliotransmitters. A central tenet is that astroglial intracellular Ca2+ signals promote release of such signaling substances, either through synaptic or non-synaptic mechanisms. Accruing evidence suggests that astroglial Ca2+ signals play important roles in both seizures and epilepsy, and this review aims to highlight the current knowledge of the roles of astrocytic Ca2+ signals ictogenesis and epileptogenesis.